(NsO^INENIQ(B: [1887] / s (N~ASTX (B6s - (N~EHOW(B, (NaNTON pAWLOWI^s ((NmOSKWA(B:s (NnAUKA(B, s, 1976)
(Nw (B6 (NTOM SOBRANIQ SO^INENIJ a(B.(Np(B. (N~EHOWA WO[LI RASSKAZY NAPISANNYE (B1887 (NG(B.s
rus
Keywords: (NpOWESTI I RASSKAZYs